Bio-based Substances From Compost as Reactant and Active Phase for Selective Capture of Cationic Pollutants From Waste Water - Magnacca, Giuliana; Neves Dos Santos, Flavio; Sadraei, Razieh (Frontiers in Chemistry, 2020)
Alumina porous monoliths were successfully fabricated using a simple and reproducible synthesis dispersing gamma alumina phase from commercial boehmite (GAB) in water containing water soluble Bio-Based Substances (BBS) obtained from composted biowaste. The wet mixture obtained was shaped in form of small spheres, then dried and calcined at 500°C in order to burn the organic matter and obtain mesoporous monoliths. They were successively functionalized with BBS in order to introduce BBS functional groups and obtain an efficient adsorbing system. Therefore, in this work, BBS acted as template/binder for the production of monoliths and as functionalizing agent of the produced monoliths. The reference powders, deeply studied in a published paper (Sadraei, Paganini, Calza, Magnacca, 2019), and the monoliths of GAB before and after functionalization were characterized by means of X-Ray Diffraction (XRD) to evidence their crystal structure, Fourier transform infrared spectroscopy (FT-IR) for evaluating the presence of BBS on the supports, thermogravimetric analysis (TGA) to measure the thermal stability of the materials and quantify the functionalizing BBS amount immobilized on the supports, nitrogen adsorption at 77K for the investigation of the surface area and porosity of the systems, zeta potential measurements to analyze the effect of BBS immobilization on the surface charge of the supports and to predict the type of interaction which can be established with substrates. Finally, the systems were applied in removal of pollutants with different charge, polarity and molecular structure, such as dyes (Crystal Violet and Acid Orange 7) and Contaminants of Emerging Concern (Carbamazepine and Atenolol).